Genome-wide characterization of PEBP genes in Mung bean (Vigna radiata L.) with functional analysis of VrFT1 in relation to photoperiod - Renfeng Xue; Yu Liu; Ming Feng; Yuning Huang; Yang zhao; Jian Chen; Tao Li; Chao Zhong; Weide Ge (Scientific Reports)
Abstract Mung bean (Vigna radiata L.), a widely cultivated legume, belongs to the Fabaceae family’s Papilionoideae subfamily. Although Phosphatidylethanolamine-binding protein (PEBP) genes have been identified in several plant species, their presence and function in mung bean remain largely unexplored. In this study, we identified seven VrPEBP genes from mung bean and classified them into four clades: FT, MFT, TFL and FT-like. Cis-regulatory element analysis revealed that VrPEBP genes may play a role in light, hormone, and stress responses. Quantitative real-time PCR (qRT-PCR) analysis indicated that VrPEBPs were constitutively expressed in various tissues. However, tissue-specific expression patterns were observed among VrPEBP genes. Under short-day (SD) conditions, VrFT1 and VrMFT1 exhibited significantly higher expression levels than under long-day (LD) conditions at 8 and 4 h, respectively. Conversely, VrTFL2 and VrTFL3 showed significantly higher expression levels under LD conditions compared to SD conditions at 8 and 12 h, respectively. The varied expression patterns of these genes under different photoperiod suggest their potential involvement in the photoperiodic regulation of flowering in mung bean. Additionally, phenotypic analysis of transgenic Arabidopsis plants overexpressing VrFT1 revealed higher expression levels under SD conditions and predicted its role in promoting flowering. These results provide valuable insights into the evolution and function of PEBP genes in mung bean and lay the foundation for further research on their regulatory mechanisms and potential applications in mung bean improvement.